A retrospective study of HIV, antiretroviral therapy, and pregnancy‐associated hypertension among women in Lusaka, Zambia. Issue 3 (September 2016) - Stoner, Marie C.D.; Vwalika, Bellington; Smid, Marcela C.; George, Shalin; Chi, Benjamin H.; Stringer, Elizabeth M.; Stringer, Jeffrey S.A.
Abstract: Objective: To investigate the association between HIV, antiretroviral therapy (ART), and pregnancy‐associated hypertension (PAH) in an HIV‐endemic setting. Methods: A retrospective cohort study was undertaken of pregnant women for whom information was recorded between February 2006 and December 2012 in the Zambia Electronic Perinatal Record System, which captures data from 25 facilities in Lusaka, Zambia. PAH was defined as eclampsia, pre‐eclampsia, hypertension, or elevated blood pressure (> 140/80 mm Hg) during delivery admission. Logistic regression estimated the odds of PAH among women by HIV serostatus, and by most recent CD4 T lymphocyte count and ART status among women with HIV infection. Results: Among 249 771 women included in the analysis, 5354 (2.1%) had PAH. Compared with women without HIV infection, women with HIV infection not receiving ART had lower odds of PAH (adjusted odds ratio [AOR] 0.86, 95% confidence interval 0.78–0.95), whereas those with HIV infection who had initiated ART had higher odds of PAH (AOR 1.15, 95% CI 1.01–1.32). No association was found between PAH and timing of ART initiation or CD4 lymphocyte count. Conclusion: In a large African urban cohort, women with untreated HIV infection had the lowest odds of PAH. Treatment with ART could increase PAH risk beyond that of women without HIV infection and those with untreated infection.